PROCESS OPTIMIZATION OF DEHYDRATED MANGO SLICES - Tiu, Ann Myril C (Journal of Agriculture and Technology Management, 2015)
The main objective of this work is to determine the optimum levels of sucrose concentration, pluming time, and loading density in the dehydration process of Mango slices conducted at Cebu Technological University using Box-Benhken Design for Response Surface Methodology. Firm, rare-ripe mango was subjected to different 15 treatments. Treatments were subjected to sensory evaluation using 9-point hedonic scale and descriptive analysis. Drying time, percentage yield, and moisture content (%db) were subjected to Response Surface Regression Analysis (RSReg) to determine the degree of variance. Data revealed that the samples prepared using lower sucrose concentration have longer drying time than that of the samples using higher sucrose level. Percentage yield values of dehydrated mango slices ranged 11.40%-18.50% with an overall response mean of 14.27% or less that 20% recovery. Samples processed using higher sugar concentration and lesser loading density calculated to have higher cost. Although statistically insignificant at (P< 0.01), the differences in cents would be relatively be gigantic when converted to industrial production volume.